MODIFICATION OF THE ATTENUATION EQUATION FOR PEAK GROUND ACCELERATION (PGA) IN THE NORTH SUMATERA REGION - Rahma, Sauma Natia; Lubis, Lailatul Husna; Sirait, Ratni; Pratama, Rian; Wijaya, Angga (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Prediction of the empirical formula for ground acceleration is an important thing to analyze for seismic estimation in an area. This needs to be done to reduce the negative impact of earthquakes as a more appropriate mitigation effort in planning and designing earthquake-resistant buildings. Therefore, the empirical formulation from Zhaou, et al is used, which is well adapted to the seismotectonic conditions of the North Sumatra region, which has high seismic vulnerability, considering that this region is located in an active subduction zone. This advantage allows the model to more accurately predict the maximum ground acceleration (PGA) produced by earthquakes in the region. The purpose of this research is to obtain an empirical formulation of the maximum ground acceleration value based on seismic parameters such as distance, depth, and magnitude. It will also show the relationship between these parameters and the value of maximum ground acceleration or peak ground acceleration (PGA) in the North Sumatra region. This study modifies the empirical formulation of Zhao, et al data sourced from the Meteorology Climatology and Geophysics Agency (BMKG) of North Sumatra in 2017-2023 with a magnitude of 3 - 6 Mw. This research uses non-linear regression with the least squares method. The results of the analysis of the empirical formula produce the constant value sought a = 1.4703 b = -0.0025, c = 20.7441, d = 0.0196, e = 0.0015, S_SS = -2.0843, and S_SL = -0.0529. An empirical formula was obtained for the North Sumatra region based on the research results. This equation can be used on a scale of 3.0 - 6.0 Mw and a distance to the earthquake source between 0 - 300 km. The relationship between each parameter of this empirical formula is that the PGA value will increase with the magnitude, and the PGA value will decrease as the epicentre distance increases.